Financial Inclusion in Sub-Saharan Africa: The Case of Mobile Money - Kemgou Voptia , Etian Boress; Stukalina , Yulia (Ekonomika, 2025)
Financial inclusion is a mechanism that provide accessibility and application of formal financial system at an affordable cost. Mobile money as a financial service allows value to be exchanged and stored in mobile money accounts as this facilitates economic development, expand investment opportunities, increase consumer spending, encourage entrepreneurship, and boost economic growth. Mobile money appears to be a good solution for accelerating financial inclusion. Research objective: This research aims to assess how mobile money can improve financial inclusion in Sub-Saharan Africa. Design/Methodology/Approach: This study utilizes secondary data from international organizations, specifically the IMF Financial Access Survey (FAS) and World Development Indicators by the World Bank. The sample consists of 17 Sub-Saharan African countries from 2010 to 2021. Financial inclusion is measured using an index developed, with data sourced from the FAS (2019) database, while mobile money usage data is also derived from the same database. To evaluate the impact of mobile money on financial inclusion, a dynamic panel model is utilized, estimated using the systemic generalized method of moments (Sys-GMM), drawing on methodology’s framework for robust estimation. Results: The results confirm the central hypothesis, according to which the use of mobile money improves financial inclusion in Sub-Saharan Africa. It is therefore up to States and mobile network operators to intensify the use of mobile money. This intensification would be possible thanks to the development of mobile money, the regulation and security of mobile money services. Originality / Value / Practical implications: This research contributes novel insights into the role of mobile money as a transformative tool for financial inclusion in Sub-Saharan Africa. It distinguishes between registered and active mobile money accounts, assessing their effectiveness in facilitating access to traditional banking services such as loans, bill payments, savings, and overdrafts. By understanding user behaviors and engagement, this study provides a nuanced perspective on the impact of mobile money on the financial landscape of the region Implication: The results enable the formulation of strategic recommendations for policy-makers aimed at advancing economic policies that foster the growth and utilization of mobile money services. These policies may include fostering partnerships between governments and mobile operators, enhancing digital literacy programs for users, and implementing regulatory frameworks that protect user interests while promoting innovation within the mobile money sector.